Q: WHAT IS O plus S equals R?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

15 and 24, respectively.

R = S + 2T S = 3T .... substitute R = (3T) + 2T R = 5T

r + s = 4 and 2r + 3s = 8 multiply the first equation by 2 giving 2r + 2s = 8 subtract this from the second equation giving s = 0 So r = 4 and s = 0.

s = -70

Surface Area = pi*r*s + pi*r*r = 3.14*2*9 + 3.14*2*2

Related questions

v

15 and 24, respectively.

Congratulations! You already have. h = S+r

R = S + 2T S = 3T .... substitute R = (3T) + 2T R = 5T

r + s = 4 and 2r + 3s = 8 multiply the first equation by 2 giving 2r + 2s = 8 subtract this from the second equation giving s = 0 So r = 4 and s = 0.

r and s can be any values such that r + s = 39. The answer is indeterminate since there are many solutions for that expression. If the new expression is included, then there must be some r and s for the problem.

R = s + 2t; s = 3tR = 3t + 2tR = 5t

Given T = R + RS Lateral inversion makes it to be R + RS = T Taking R as common factor, we get R(1+S) = T Now dividing by (1+S) both sides, R = T / (1+S) Hence the solution R = T/(1+S)

Since r varies directly with s, we have r = ks (replace k with 5 and s with 7) r = (5)(7) r = 35

S = 2 pi r h + 2 pi r2S - 2 pi r2 = 2 pi r hh = (S - 2 pi r2) / (2 pi r)

it does not change -apex

i think S=9 e=5 n=6 d=7 m = 1 o =0 r = 8 y =2